Rekayasa Sosial dan Tanggung Jawab Hukum Negara dalam Program Kesehatan Ibu Anak-Keluarga Berencana - Acep Wahyu; Joko Sriwidodo; R Lina Sinaulan (JURNAL HUKUM PELITA, 2025)
This article examines how the state employs law as an instrument of social engineering in implementing the Maternal and Child Health and Family Planning (KIA–KB) program. Drawing on Roscoe Pound’s theory of law as a tool of social engineering, the study argues that law functions not merely as an administrative mechanism, but as a means of social transformation designed to build public awareness regarding reproductive responsibility, maternal and child health, and family welfare. The discussion is grounded in the constitutional and legal foundations of the state’s responsibility as enshrined in Article 28H and Article 34(3) of the 1945 Constitution, Law No. 36 of 2009 on Health, and Law No. 52 of 2009 on Population Development and Family Development. The analysis reveals that the KIA–KB program represents a form of state intervention in shaping social behavior, yet its implementation faces dilemmas between collective social objectives and individual bodily autonomy, gender justice, and moral and cultural values. Issues such as unequal distribution of contraceptives, coercive practices toward low-income women, and weak reproductive education reflect ethical deficiencies in the state’s legal responsibility. Therefore, the article emphasizes the need for a humanistic and rights-based model of legal responsibility that ensures distributive justice, respect for bodily autonomy, and gender equality in reproductive health services. The study concludes that the success of health law should not be measured by the extent of state control over population behavior, but by how effectively it safeguards human rights, social welfare, and substantive justice for all citizens